APPLICATION OF LIQUID SMOKE RAMBUTAN ON WOOD FISHERY PRODUCTS CATFISH (Pangasius hypopthalmus) SMOKE COMMUNITY XIII KOTO KAMPAR - Vella Srinovita; Sukirno Mus; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The aim of this study was to develop science and technology for the public to provide information on the quality of smoked fish that are processed using traditional liquid smoke and fumes. The use of liquid smoke and fumes traditionally expected to be an alternative curing methods that are environmentally friendly, pose no danger carcinogens, as well as producing good quality smoked fish. The study uses the completely randomized design (CRD).The treatment is traditionally smoked catfish (At), catfish pyrolysis liquid smoke (Ap) and cathish liquid smoke destillate (Ad) to repeat 3 times.Results of research conducted on smoked catfish with different curing that panelists preferred the rough catfish liquid smoke (pyrolysis). Based on organoleptic assessment (fine aroma, taste and texture), catfish with AP treatment has the best quality compared to other treatments with such characteristics intact, clean, brown, shiny very specific kind. Less fragrant aroma, smell smoke enough without additional intrusive. Taste and less savory. Dense texture is compact, dry, tightly categorized between good tissue and meet (SNI.2725.1: 2009) as well as chemical assessment protein content, ash content and moisture content are also the best value while nilaipH AP treatment and total phenol best value, namely the treatment of AD.Keyword : Liquid smoke, Catfish, Quality